Thyrotoxic Periodic Paralysis Causing Back Pain and Leg Weakness: An Unusual Presentation of Hyperthyroidism - Henrik Elenius; Marie Cesa; Corina C. Nava Suarez; Abhishek Nimkar; Prasanta Basak; Nandita Sinha (Case Reports in Endocrinology)
Thyrotoxic periodic paralysis (TPP) is a rare muscular disorder, characterized by muscle weakness and hypokalemia triggered by thyrotoxicosis. In Asian populations, 2% of patients with thyrotoxicosis are affected, compared to only 0.1–0.2% of non-Asians. The vast majority of patients are male. Muscle weakness ranges in severity from very mild to life-threatening, due to respiratory compromise. We present a case of a previously healthy 39-year-old Hispanic male who presented with sudden quadriparesis and quickly recovered after being treated for hypokalemia and thyrotoxicosis. TPP, although unusual, is important to recognize as it is a potentially fatal condition that requires close monitoring and is readily reversible with appropriate therapy. Any cause of thyroid hormone excess can cause TPP, with Graves’ disease being the most common etiology. Acute treatment includes potassium repletion, while long-term management focuses on determining and treating the cause of thyrotoxicosis, since maintaining a euthyroid state will prevent further episodes of TPP.